Repurposing major metabolites of lamiaceae family as potential inhibitors of α-synuclein aggregation to alleviate neurodegenerative diseases: an in silico approach - Bhattacharya, Soham; Gupta, Neha; Dutta, Adrish; Khanra, Pijush Kanti; Dutta, Ritesh; Žiarovská, Jana; Tzvetkov, Nikolay T.; Severová, Lucie; Kopecká, Lenka; Milella, Luigi; Fernández-Cusimamani, Eloy (Frontiers in Pharmacology, 2025)
Neurodegenerative disorders (NDs) are typically characterized by progressive loss of neuronal function and the deposition of misfolded proteins in the brain and peripheral organs. They are molecularly classified based on the specific proteins involved, underscoring the critical role of protein-processing systems in their pathogenesis. Alpha-synuclein (α-syn) is a neural protein that is crucial in initiating and progressing various NDs by directly or indirectly regulating other ND-associated proteins. Therefore, reducing the α-syn aggregation can be an excellent option for combating ND initiation and progression. This study presents an in silico phytochemical-based approach for discovering novel neuroprotective agents from bioactive compounds of the Lamiaceae family, highlighting the potential of computational methods such as functional networking, pathway enrichment analysis, molecular docking, and simulation in therapeutic discovery. Functional network and enrichment pathway analysis established the direct or indirect involvement of α-syn in various NDs. Furthermore, molecular docking interaction and simulation studies were conducted to screen 85 major bioactive compounds of the Lamiaceae family against the α-syn aggregation. The results showed that five compounds (α-copaene, γ-eudesmol, carnosol, cedryl acetate, and spathulenol) had a high binding affinity towards α-syn with potential inhibitory activity towards its aggregation. MD simulations validated the stability of the molecular interactions determined by molecular docking. In addition, in silico pharmacokinetic analysis underscores their potential as promising drug candidates, demonstrating excellent blood-brain barrier (BBB) permeability, bioactivity, and reduced toxicity. In summary, this study identifies the most suitable compounds for targeting the α-syn aggregation and recommends these compounds as potential therapeutic agents against various NDs, pending further in vitro and in vivo validation.